Accessing dental anxiety online support groups: An exploratory qualitative study of motives and experiences - Buchanan, Heather; Coulson, Neil S.
Objectives: In recent years, Internet access has grown markedly providing individuals with new opportunities for online information retrieval, psychological advice and support. The objectives of the present study were to explore the context through which dentally anxious individuals access an online support group and the nature of their online experiences. Methods: An online questionnaire was completed by 143 individuals who accessed the Dental Fear Central online support group bulletin board. Qualitative analysis was conducted on the responses. Results: Analysis revealed three emergent themes which reflected the motives and experiences of individuals: ‘Searching for help’, ‘Sharing fears’ and ‘I feel empowered’. Conclusion: This exploratory study suggests that for most individuals accessing this online support group was a positive and beneficial experience. Practice Implications: Online support groups may represent a convenient and beneficial tool that may assist certain individuals to confront their debilitating anxiety/phobia and successfully receive dental care.